2016
DOI: 10.1002/2016jd025311
|View full text |Cite
|
Sign up to set email alerts
|

Fine particle pH and the partitioning of nitric acid during winter in the northeastern United States

Abstract: Particle pH is a critical but poorly constrained quantity that affects many aerosol processes and properties, including aerosol composition, concentrations, and toxicity. We assess PM1 pH as a function of geographical location and altitude, focusing on the northeastern U.S., based on aircraft measurements from the Wintertime Investigation of Transport, Emissions, and Reactivity campaign (1 February to 15 March 2015). Particle pH and water were predicted with the ISORROPIA‐II thermodynamic model and validated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
378
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 245 publications
(415 citation statements)
references
References 152 publications
22
378
3
Order By: Relevance
“…However, it is worth noting that particle acidity is not likely a factor in the relative split between reversible and irreversible aqSOA formed from isoprene. Studies predict that particles in the eastern USA are highly acidic throughout the year Battaglia et al, 2017;Guo et al, 2016Guo et al, , 2015, and acidity is not a limiting factor in isoprene SOA formation during the summer Xu et al, 2015). The implication from our observations is that reversible aqSOA from isoprene forms even in the presence of such persistently acidic particles.…”
Section: Atmospheric Implicationssupporting
confidence: 51%
“…However, it is worth noting that particle acidity is not likely a factor in the relative split between reversible and irreversible aqSOA formed from isoprene. Studies predict that particles in the eastern USA are highly acidic throughout the year Battaglia et al, 2017;Guo et al, 2016Guo et al, , 2015, and acidity is not a limiting factor in isoprene SOA formation during the summer Xu et al, 2015). The implication from our observations is that reversible aqSOA from isoprene forms even in the presence of such persistently acidic particles.…”
Section: Atmospheric Implicationssupporting
confidence: 51%
“…The model performance has been evaluated against comprehensive ambient datasets over a wide range of acidities, RH and temperatures (Fountoukis and Nenes, 2007;Fountoukis et al, 2009;Hennigan et al, 2015;Guo et al, 2015;Weber et al, 2016;Guo et al, 2016). In our analysis, we also consider the contribution of hygroscopic organics to the water uptake of the aerosol using the approach of Guo et al (2015).…”
Section: Hygroscopic Growth Modelmentioning
confidence: 99%
“…Both organic and inorganic compounds contained within aerosol can drive the formation of a liquid aerosol phase (e.g., Guo et al, 2016). Aerosol water uptake changes the particle size and refractive index with profound implications for radiative transfer and cloud formation (e.g., Quinn et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…(2-5) respectively. Although they are straightforward to calculate, a few recent studies (Murphy et al, 2017;Hennigan et al, 2015;Guo et al, 2016) have demonstrated that the ion balance and equivalent ratio calculated from ambient particle measurements…”
Section: Ion Balance and Equivalent Ratiomentioning
confidence: 99%